2022
DOI: 10.1111/aej.12615
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calcium silicate‐based cements on odonto/osteogenic differentiation potential in mesenchymal stem cells

Abstract: The objective of this study was to evaluate the biological effects and odonto/osteogenic differentiation potential of Biodentine, NeoMTA Plus and TheraCal LC in tooth germ‐derived stem cells (TGSCs). TGSCs were exposed to the material extracts. Biocompatibility was tested with MTS cell proliferation assay. Odonto/osteogenic differentiation was assessed with alkaline phosphatase (ALP) activity and mRNA gene expressions (RUNX2, DSPP and DMP‐1). Scanning electronic microscopy/energy‐dispersive X‐ray (SEM/EDX) ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…In the defect areas where nMTA was placed, immature bone formation was observed at a rate of 54.3% on the 7th day and 28.6% on the 14th day. The remarkable results of our research on nMTA corroborate those of many studies that have highlighted the superior properties of the material 9 , 37 , 38 .…”
Section: Discussionsupporting
confidence: 89%
“…In the defect areas where nMTA was placed, immature bone formation was observed at a rate of 54.3% on the 7th day and 28.6% on the 14th day. The remarkable results of our research on nMTA corroborate those of many studies that have highlighted the superior properties of the material 9 , 37 , 38 .…”
Section: Discussionsupporting
confidence: 89%
“…Isolated from the tooth germs of third molars, which can be considered a more primitive tissue present during young adulthood compared to more developed pulp and apical papilla tissues, tooth germ-derived MSCs are multipotent stem cells that can benefit from interactions between ectoderm and mesoderm as they are derived from epithelial cells and the underlying mesenchyme [15]. Recent studies reported a high osteo/odontogenic potential for tooth germ-derived MSCs both in vivo and in vitro, alone or in combination with scaffolds [11,13,16]. Hence, the present study used tooth germ-derived MSCs to demonstrate if MTA-based biomaterials can support the induction of odontogenesis and maintain viability.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were prepared as discs 5 mm in diameter and 3 mm thick in pre-sterilized Teflon ® molds in a laminar flow under aseptic conditions using the manufacturer's recommendations. Material extracts were prepared as previously described [13]. All prepared samples were incubated at 37 • C for 6 h. Samples were exposed to UV light at room temperature for 1 h. After sterilization, sample discs were submerged into 1 mL of growth medium and kept in a 90% humidified atmosphere of 5% CO 2 for a day.…”
Section: Preparation Of Materials Extractsmentioning
confidence: 99%
“…The findings related to Biodentine could be explained by its ability to induce differentiation of pulp stem cells and increased expression of dentin sialoprotein and alkaline phosphatase activity 30) . Complete or partial dentin bridges were primarily detected during 4 weeks, with enhanced continuity and thickness by 8 weeks.…”
Section: Discussionmentioning
confidence: 99%